Power line communication: implementação Internet das Coisas (IoT) para automação residencial - Almeida, Leonardo Mudrek de (2021)
As a viable possibility for automation aimed at innovation and the use of new methods, the present study lists an alternative in the construction of a home automation ecosystem, with central and peripheral modules. The interaction between the devices brings the active use of communication through the electric power cabling, widely available in today’s residential environments, using the PLC technique. In this sense, promoting the use of recent technologies for the theme, brings the provocation and action of expansion of art as a whole, fermenting new studies and discussions. The prototype system is based on a concentrator (CCO) and a station (STA), the communication between the devices and with the end user takes place using the PLC 3121N-H module and the ESP-WROOM -32U, respectively. As an automation application in this work, the station receives commands from the concentrator via a wired network to activate a load connected to its output, with switching via thyristor. In the interaction with the user, the system embeds a WEB interface with robust architecture, efficient and simple coupling with other consumers, characteristics present in the denotation of a API. As for the results, the application in a residential environment showed that the maximum distance between the modules in the electrical network was 50 meters. The interaction with the proposed system, through an API, demonstrates the capacity in the expansion of automation applications to use the PLC scope, promoting consumption through a computer or cell phone, for example.